Zmiany składu wód podziemnych w otoczeniu meromiktycznego, acidotroficznego zbiornika kopalnianego = The variation of chemical composition of grounwater located in the surroundings of meromictic, acidotrophic pit reservoir - Jachimko, Barbara; Kruk, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of the research on chemical composition of groundwater located in the surroundings of acidotrophic pit reservoir are presented. The research were conducted during one year in three piezometers situated: one recharge and two on the opposite sides. The chemical composition of waters in piezometers differed significantly. All waters had features of acid mine drainage, especially in the aspects of pH value, iron and sulphate concentrations. The substantial changes for the worse of groundwater quality due to contact with reservoir water were stated.
Keywords: zbiorniki kopalniane; kwaśne wody kopalniane; meromiksja; post-mining reservoirs; acid mine drainage; meromixis